2018
DOI: 10.1038/s41598-018-29261-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between complete genomes of an isolate of Pseudomonas syringae pv. actinidiae from Japan and a New Zealand isolate of the pandemic lineage

Abstract: The modern pandemic of the bacterial kiwifruit pathogen Pseudomonas syringae pv actinidiae (Psa) is caused by a particular Psa lineage. To better understand the genetic basis of the virulence of this lineage, we compare the completely assembled genome of a pandemic New Zealand strain with that of the Psa type strain first isolated in Japan in 1983. Aligning the two genomes shows numerous translocations, constrained so as to retain the appropriate orientation of the Architecture Imparting Sequences (AIMs). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Our Psa2 and Psa3 strains featured the canonical EEL structure (including tRNA Leu , queA and tgt sequences) although two of the three Psa2 genomes (ICMP 19071 and ICMP 19072) contained a phage insertion within the EEL, supporting the observation that tRNA genes are often found at phage integration sites (75). Multiple rearrangements have been reported in Psa1 and Psa3 biovars (76), and accordingly we found that the tRNA Leu , queA and tgt sequences were dispersed to other chromosomal locations in Psa1 (ICMP9617 and ICMP9853). Such rearrangements may be selectively neutral, but the genome structure may affect transcriptional regulation (76).…”
Section: Genomic Analysis Reveals New Features Of the Ttss-related Pasupporting
confidence: 78%
“…Our Psa2 and Psa3 strains featured the canonical EEL structure (including tRNA Leu , queA and tgt sequences) although two of the three Psa2 genomes (ICMP 19071 and ICMP 19072) contained a phage insertion within the EEL, supporting the observation that tRNA genes are often found at phage integration sites (75). Multiple rearrangements have been reported in Psa1 and Psa3 biovars (76), and accordingly we found that the tRNA Leu , queA and tgt sequences were dispersed to other chromosomal locations in Psa1 (ICMP9617 and ICMP9853). Such rearrangements may be selectively neutral, but the genome structure may affect transcriptional regulation (76).…”
Section: Genomic Analysis Reveals New Features Of the Ttss-related Pasupporting
confidence: 78%
“…Genome sequencing yielded an average of 1.05 million paired sequence reads for each genome, equivalent to an average 40-fold read coverage. The sequence reads from the Psa3 isolates were mapped to the completely assembled 6 555 571 bp chromosome and 74 432 bp plasmid of a pandemic Psa3 strain from New Zealand, ICMP18708 (GenBank accessions CP012179-chromosome and CP012180-plasmid [26]), using Geneious 11.0.3 [39]. Read mapping was performed with the Geneious 6.0.3 Read Mapper [40] using the following parameter values: maximum mismatches per read=10 %, minimum mapping quality=Phred 30, maximum gaps per read=10 % read length, maximum gap length=3 bp and minimum overlap=25 bp.…”
Section: Wgs Analysismentioning
confidence: 99%
“…The genomes of several isolates of Psa have been fully sequenced using the PacBio platform [26,41]. This permitted the identification of RM systems specific to different types of Psa.…”
Section: Rm Systems In Psa3mentioning
confidence: 99%
See 2 more Smart Citations